RNA methylation by Dnmt2 protects transfer RNAs against stress-induced cleavage - Schaefer, Matthias R.; Pollex, Tim; Hanna, Katharina; Tuorto, Francesca; Meusburger, Madeleine; Helm, Mark; Lyko, Frank (Genes & development, 2010)
Dnmt2 proteins are the most conserved members of the DNA methyltransferase enzyme family, but their substrate specificity and biological functions have been a subject of controversy. We show here that, in addition to tRNAAsp-GTC, tRNAVal-AAC and tRNAGly-GCC are also methylated by Dnmt2. Drosophila Dnmt2 mutants showed reduced viability under stress conditions, and Dnmt2 relocalized to stress granules following heat shock. Strikingly, stress-induced cleavage of tRNAs was Dnmt2-dependent, and Dnmt2-mediated methylation protected tRNAs against ribonuclease cleavage. These results uncover a novel biological function of Dnmt2-mediated tRNA methylation, and suggest a role for Dnmt2 enzymes during the biogenesis of tRNA-derived small RNAs.